IMPLEMENTASI SISTEM AKUNTANSI INSTANSI BERBASIS AKRUAL (SAIBA) PADA BALAI DIKLAT KEAGAMAAN PROVINSI ACEH - Kasfari, Andi; Abdullah, Syukriy (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
The purpose of this study provides a description of the impact and challenges in the implementation of the Accrual-Based Agency Accounting System (SAIBA). This research was conducted at the Religious Training Center in the Province of Aceh. Type of qualitative research with data collection based on interview techniques, observation and documentation studies. Data is obtained by going down directly to the research location and reviewing it with existing literature studies. This research is expected to be useful for the staff of the Aceh Province Religious Training Center in implementing accrual-based accounting to run optimally. The results show that the Implementation of Accrual-Based Agency Accounting System at the Center for Religious Training in Aceh Province has not been so effective. The problem is related to the readiness of human resources who have not fully understood accrual-based accounting. However, the implementation of accrual-based accounting has brought significant benefits. Challenges in the implementation of accrual-based accounting in terms of leadership commitment, the Aceh Province Religious Training Center supports changes in accrual-based accounting because clear and absolute regulations regarding systems, procedures, and policies are regulated in PP 71 of 2010. Accounting systems and IT facilities and infrastructure have been adequate. As a form of anticipation of the emergence of staff resistance, the strategy carried out in the form of socialization as well as training was intensified in early 2015 but there was a decline in the following year. Resistance appears on two considerations, namely the ease and benefits of implementing SAIBA. The response of the staff of the Aceh Province Religious Training Center is that it is easy to run the SAIBA application for those who have mastered and can facilitate staff performance. On the other hand, there are benefits obtained from the SAIBA application as financial reports are more transparent and accurate.